HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP KADAR BILIRUBIN PADA BAYI 0 – 2 HARI HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP KADAR BILIRUBIN PADA BAYI 0 – 2 HARI - Suzanna Fabella Putri; Dewa Ayu Sri Saraswati; Suyati (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction: bilirubin is a jaundiced orange crystalline pigment which is the final form of breaking down the word heme bolism through a process of oxidation-reduction reactions which as much as 75% comes from hemoglobin and from 25% from heme in the liver, muscle myoglobin. The lack of breast milk in the first 0-2 days after birth can cause jaundice in babies. The aim of this study : was to determine the relationship between exclusive breastfeeding and bilirubin levels in infants 0-2 days at RSIA Cinta Kasih Ciputat in 2020. Research method: this uses a cross sectional approach method. The population is infants 0-2 days who are treated at RSIA Cinta Kasih. The sample in this study were 48 respondents who were determined by using the Porposive Sampling technique. The research instrument was an observation sheet. Analysis of research data using the Chi Square test. The results: showed that it was found that out of 48 respondents who were given exclusive breastfeeding, 18 respondents (37.5%) were not exclusively breastfed as many as 30 (62.5%). Of the 48 respondents, there were 13 (27.1%) respondents with normal bilirubin levels, 35 (72.9%) respondents with abnormal bilirubin levels. Conclusion: there is a relationship between exclusive breastfeeding and bilirubin levels in infants 0-2 days (P value = 0.001). Suggestion: it is hoped that the nurse will be able to provide education or counseling to all new mothers about exclusive breastfeeding on bilirubin levels so that in the future it can improve the quality of service better.